Indonesia - Fera Alfiani; Sri Kurniasih (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
Abstract Cinematography Educational Park located in Menteng, Jakarta Pusat, is a building that facilitates the society/community, especially for the appreciators in film industry such as audiences and filmmakers. The design of Cinematography Educational Park will carry a concept of Futuristic Architecture. Futuristic Architecture is a style of architecture that orientates toward the future. The product of this design is expected to be surprising, peculiar and eccentrice.